Eccrine angiomatous hamartoma treated with multimodal vascular laser and incobotulinum - Yaron Gu; Kelvin Truong; Steven Kossard; Adrian Lim; Deshan F. Sebaratnam (Wiley, 2024)
Abstract Eccrine angiomatous hamartoma (EAH) is a rare benign vascular lesion that is distinguished histologically by vascular and eccrine overgrowth. We report the case of a 46‐year‐old woman with EAH who was successfully treated with multimodal incobotulinum toxin A, pulsed dye laser and long‐pulsed neodymium‐doped yttrium aluminium garnet laser.